The Impact of Science Learning Materials Integrating Natural Disasters and Disaster Mitigation on Students' Learning Outcomes: A Meta Analysis - Asrizal Asrizal; Nur Hikmah; Dhea Febriya; Filda Mawaddah (Postgraduate, University of Mataram, 2023)
This research is a meta-analysis to determine the impact of science teaching materials integrated with natural disasters and disaster mitigation on students' learning outcomes. The method used is meta-analysis with research samples, namely scientific articles that have been published through Google Scholar on a national and international scale in 2012-2022, which discuss integrated science teaching materials on natural disasters and disaster mitigation on student learning outcomes. The results of the study showed that science teaching materials integrated with natural disasters and disaster mitigation had a large effect on student learning outcomes. In the category of teaching materials, the science module, which integrates natural disasters and disaster mitigation materials, has the highest effect. In the category where natural disaster materials and disaster mitigation are integrated, disaster mitigation materials have the highest effect compared to natural disaster materials. And in the school level category, the application of integrated science teaching materials on natural disasters and disaster mitigation has a high effect when applied to the Junior and Senior High School Levels, with a higher impact on the Junior High School level